A murder is announced - Christie, Agatha 1890-1976 (New York Berkley Books, 1991)
Miss Jane Marple finds herself a player in a party murder game which ends up with a real corpse.
Keywords: Marple, Jane (Fictitious character) -- Fiction; Women detectives -- England -- Fiction; Mystery fiction